A critical review on the adaptability of ventilation systems: Current problems, solutions and opportunities. (15th March 2022) - Seuntjens, O.; Belmans, B.; Buyle, M.; Audenaert, A.
Abstract: At present many buildings, that are not able to meet the changing needs of owners and users, are demolished before they reach their technical lifespan. To avoid such waste, the construction industry is shifting to adaptable building practices. Comfort systems in buildings that can effectively deal with an adaptable context are critical to the success of this transition. After all, these systems must ensure that the health and comfort of occupants is guaranteed in all possible flexibility scenarios. In practice, comfort systems that provide ventilation strongly adhere to firmly rooted approaches with limited adaptability. Moreover, implementing adaptability does not happen at the conceptual level, but is achieved by oversizing components and incorporating demand control. Alternative ventilation systems that are conceptually more compatible with an adaptable context are rarely even considered. To fill this knowledge gap, this review article identifies and uses various adaptability characteristics of ventilation systems to qualify both contemporary and innovative ventilation systems based on their ability to facilitate a flexible building use. By juxtaposing the systems, the article goes beyond the state-of-the-art and learns from the meta-level rather than individual cases. It is concluded that traditional ventilation strategies do not provide the most appropriate solution for an adaptive context, that bulky ductwork is incompatible with long-term flexible building use, and that specific guidelines for designing adaptable ventilation systems are lacking. Further research should look into this and additionally quantify the environmental and financial benefits of adaptable ventilation systems through life cycle assessment and life cycle cost evaluation. Highlights: Specific guidelines to design adaptable ventilation systems are lacking. Voluminous ductwork is not compatible with a long-term flexible building usage. Innovative ventilation strategies have a potential in terms of adaptability. LCA & LCCA should be carried out to quantify the impacts in the design phase.